(untitled) (Research, Society and Development, 2020)
This study aimed to identify the actions developed in / with the elderly by caregivers during hospitalization, the facilities and difficulties experienced. Descriptive and exploratory qualitative research. 11 family caregivers participated. They are characterized by their gender, daughters of the elderly, married, with children, without gainful employment. The results showed that the caregiver develops actions construed as similar to home as hygiene, nutrition, physical and emotional security. The facilities were identified: access to specialized services and the nursing staff. The difficulties were: risk of infection, lacking adaptations to receive the senior and the caregiver, caregiver stress experienced by hospital privacy and lack of physical structure. It was realized that accepting the caregiver and the elderly through information on the rules and routines of the hospital and the treatment provided to hospitalized elderly may alleviate the suffering of experiencing, along with the elderly, hospitalization.